2021
DOI: 10.3390/agriculture11090900
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Boswellia sacra Resin on Immunity, Metabolic Status, Udder and Uterus Health, and Milk Production in Transitioning Goats

Abstract: As an attempt to prevent transition-period-associated metabolic disorders and/or diseases, the potential benefits of Boswellia sacra (Bs) resin on hematology, immunity, metabolic status, udder and uterus health biomarkers, and milk production were examined in transitioning goats. From 2 weeks prepartum to 7 weeks postpartum, goats (n = 7/treatment) orally received 0 (control, nBS), 2 (BsL), or 4 (BsH) g of Bs resin/goat/day. The results showed that both Bs treatments significantly improved the activity of phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Therefore, in this study, we have focused on studying the changes in these two pathways in heat-stressed and MEONE-supplemented rabbits. Giving in mind that essential oils can alleviate the negative effects of HS through controlling these two major cells damaging pathways, oxidative and inflammatory pathways [6,14,41,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in this study, we have focused on studying the changes in these two pathways in heat-stressed and MEONE-supplemented rabbits. Giving in mind that essential oils can alleviate the negative effects of HS through controlling these two major cells damaging pathways, oxidative and inflammatory pathways [6,14,41,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the supplementation of rabbit diets with MEONE resulted in significant improvements in humoral immunity, as indicated by the increased lysosomal activity and concentration of amyloid A. The improved lysozyme activity may contribute to the elimination of pathogens because of its enzymatic degenerative potential [48,53], and amyloid A has a significant immunological activity either by being chemotactic for mast cells and neutrophils or by stimulating the synthesis of cytokines [54]. These positive effects of MEOE on immune system can be attributed to its wide biological activities, including anti-allergic, anti-inflammatory, antiviral, and antimicrobial activities [55].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that injections of recombinant bovine TNF, a proinflammatory cytokine, can induce remarkable changes in the concentrations of blood plasma glucose, triglycerides, and NEFA in Holstein heifers [ 51 ]. Generally, the reduction in this metabolite is associated with better immune functions, energy status, and reproductive performance in dairy animals [ 52 ]. For example, prolonged exposure to circulating NEFA and β-hydroxybutyrate during late prepartum and early postpartum periods was associated with impairment of PMN function during the transition period in dairy cows [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The individual milk yield was determined on a weekly basis by keeping the newborn kids in separate pens for 20 h and milking the goats by hand until the udder was empty throughout the suckling period. The milk yield of each goat was recorded and multiplied with a correction factor of 1.2 to obtain the DMY [ 9 ].…”
Section: Methodsmentioning
confidence: 99%